Temporal Variation of Earthworm Impacts on Soil Organic Carbon under Different Tillage Systems - Guo, Yafei (Int J Environ Res Public Health, 2019)
Previous research has shown the varied effect of earthworms on soil carbon dynamics. We carried out a 180-day incubation experiment with earthworms and maize residue additions under conventional tillage (CT) and no tillage (NT) system conditions to quantify the earthworm effect in the black soil of northeastern China. Earthworms did not affect soil CO(2) emissions, while residue addition significantly increased such emissions. The effects of earthworms on dissolved organic carbon (DOC) and microbial biomass carbon (MBC) gradually weakened with time in CT with and without residue addition, but gradually increased with time in NT with residue addition. In the CT system, earthworms accelerated the soil organic carbon (SOC) mineralization; and the newly added residue decomposed into SOC. In the NT system, earthworms accelerated the decomposition of native residues increasing the SOC content; this increase in decomposition rates by earthworms was greater than the inhibitory effect imposed by the addition of the new residue. Earthworms and residues combine to play a single role in CT and NT. This result will help in the understanding of the role of earthworms and residue in SOC dynamics, and in the development of management strategies to improve SOC.